2011
DOI: 10.3996/012011-jfwm-003
|View full text |Cite
|
Sign up to set email alerts
|

A Markov Decision Process for Managing Habitat for Florida Scrub-Jays

Abstract: Florida scrub-jays Aphelocoma coerulescens are listed as threatened under the Endangered Species Act due to loss and degradation of scrub habitat. This study concerned the development of an optimal strategy for the restoration and management of scrub habitat at Merritt Island National Wildlife Refuge, which contains one of the few remaining large populations of scrub-jays in Florida. There are documented differences in the reproductive and survival rates of scrub-jays among discrete classes of scrub height (&a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 25 publications
1
47
0
2
Order By: Relevance
“…Because scrub regrowth is often a function of underground biomass, many ecologists have observed that tall scrub recovers much faster than scrub that has been subjected to frequent fires [9]. Fire managers usually rely on a return interval to determine when a managed area needs to burn, which differs from the typical ARM approach, which recommends using current values of time-specific state variables (e.g., habitat states from Table 1) to determine the optimal management action [18].…”
Section: Management Of Florida Scrub: Fuel Management Vs Ecological mentioning
confidence: 99%
See 4 more Smart Citations
“…Because scrub regrowth is often a function of underground biomass, many ecologists have observed that tall scrub recovers much faster than scrub that has been subjected to frequent fires [9]. Fire managers usually rely on a return interval to determine when a managed area needs to burn, which differs from the typical ARM approach, which recommends using current values of time-specific state variables (e.g., habitat states from Table 1) to determine the optimal management action [18].…”
Section: Management Of Florida Scrub: Fuel Management Vs Ecological mentioning
confidence: 99%
“…Funding for conducting prescribed fires is often specified for fuel management and not necessarily for species habitat management; administrators from agencies often measure the performance of prescribed fire programs using the acreage burned each year, which provides little information on scrub habitat quality trajectories, because fire intensity and outcomes are heterogeneous [10]. Our studies have shown that an emphasis on fuel management will not achieve species conservation goals on many conservation lands [9,18]. Wildland fire managers and ecologists agree that prescribed fires can be beneficial, and we believe that differences in management approaches are reconcilable, but require stakeholders to acknowledge multiple values and agree: (1) on the legitimacy of objectives arising from these values; (2) on how to measure whether management is attaining those objectives; and (3) on how decisions should be made.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations